EFFECT OF FOLIAR SPRAY OF ZINC AND lIQUORICE ROOT EXTRACT ON SOME VEGETATIVE AND FLOWERING GROWTH PARAMETERS OF TWO STRAWBERRY VARIETIES (Fragaria x ananassa Duch.) - Zuhair A. Dawood (Mesopotamia Journal of Agriculture)
This research conducted during the growing season, 2006/ 2007 at the department of Horticulture and landscape design, college of Agriculture and forestry, Mosul university, IRAQ. The goals of this study was to investigate the effect of three concentrations of zinc element (0, 50 and 100 mg zn/L) and three concentration of liquorice root extract (0, 2 and 4gm/L) used as a foliar spray on vegetative and flowering parameters of two strawberry varieties (Hapil and Kaiser's samlling). A spilt-split plot within RCBD design with three replicates (each include 12 plants) was applied in this research . All data were teasted by using Duncan's multiple range teast under 5% level. Results obtained indicated that, Hapil variety significantly overtopped in average single leaf area, number of rooted stolensو total chlorophyll content and percentage of flowers set, while kaiser's samilng variety significantly superior in both number of crowns and flower's per plant. Spraying of 100 mg/L of zinc caused a significant increase in both number of crowns and flowers per plant. At the same time, the second conc. of liquorices (2 gm/L) gave a significant increase in average leaf area and foliage dry weight, but the third conc. (4gm/L) of liquorices caused a significant increase in both number of stolen and flowers per plant and total chlorophyll content.An additional increases were noticed in some vegetative and flowering parameters in both strawberry varieties by applying both bi or third interaction treatments.